Visualizing basic accounting flows: does XBRL + model + animation = understanding? - Marshall,Byron; Mortenson,Kristian; Bourne,Amy; Price,Kevin; Marshall,Andrew (American Accounting Association 18th Annual Strategic and Emerging Technologies Research Workshop, 2009)
The usefulness of XBRL (eXtensible Business Reporting Language) in facilitating efficient data sharing is clear, but widespread use of XBRL also promises to support more effective analysis processes. Representing traditional financial statements in this electronic and interoperable format should allow managers, investors, regulators, and importantly students to aggregate, compare and analyze financial information. Processing such data requires an understanding of the underlying paradigms embedded in consolidated sets of financial statements. This work explores the feasibility and effectiveness of an XBRL-based visualization tool, presenting an organizational framework, mapping that framework to financial statements and the XBRL formalism, and demonstrating a visual representation that organizes, depicts, and animates financial data. We show that our tool integrates and presents profitability, liquidity, financing, and market value data in a manner recognizable to business students in introductory financial accounting classes. This preliminary finding suggests the promise of XBRL-based visualization tools both in helping students grasp basic accounting concepts and in facilitating financial analysis in general.
Keywords: Accounting; BIS